Oceanario tecnologico y cientifico de fauna marina (2020)
Puerto Colombia, the tip of Barranquilla, is characterized by its beaches, its beautiful landscape and its blue Caribbean Sea, a landscape that wants to be rescued despite all the problems that this sector has. It is proposed to improve the economic boom, generate awareness towards the population about marine ecosystems and provide a space of knowledge and technology and science as support between the closest cities: Santa Marta and Cartagena. The technological and scientific oceanarium of marine fauna proposes adequate spaces for education, tourism, technology and science as mentioned above. Transparent spaces that allow permanent visibility towards the different marine species, maintaining immersion as a concept. This in order to potentiate the sector economically, nationally and internationally.